From Showroom to Click: Antecedents of Showrooming in the Omnichannel Experience - Rahmawati Rahmawati; Aang Curatman (Universitas Proklamasi 45, 2026)
This study examines how price sensitivity and trust in online sellers influence showrooming behavior, with omnichannel experience satisfaction serving as a mediator. Data were collected using a quantitative, associative design; questionnaires were administered to 165 cosmetic consumers in Cirebon, selected through purposive sampling. The data were analyzed in SmartPLS version four. The results show that price sensitivity has a positive and significant effect on showrooming behavior, whereas trust in online sellers has no significant direct effect. However, both independent variables significantly affect omnichannel experience satisfaction. Omnichannel experience satisfaction plays a significant mediating role in the relationships between trust in online sellers and price sensitivity, and showrooming behavior. These findings confirm that integrating a satisfying shopping experience is key to encouraging consumer showrooming behavior in the cosmetics retail industry. Traditional retailers should view showrooming as an opportunity for conversion by implementing integration strategies that combine the convenience of online and physical stores and ensure channel consistency.